Retraction Note: Optimized extraction, composition, antioxidant and antimicrobial activities of exo and intracellular polysaccharides from submerged culture of Cordyceps cicadae - Sapan Kumar Sharma; Nandini Gautam; Narender Singh Atri (BMC, 2018)
The editor has retracted this article [1] due to overlap with a previously published article [2]. Both articles also appear to use the same image representing different fungal mycelial growths. S.K. Sharma and N.S. Atri do not agree to this retraction. N. Gautam has not responded to correspondence from the editor about this retraction.